DEVELOPMENT OF SPEECH COMPETENCE IN FOREIGN LANGUAGE LEARNING AMONG GENERAL SECONDARY SCHOOL STUDENTS - Sobirova Intizor Mukhammatkulovna (Bright Mind Publishing, 2026)
This article investigates both the theory and the practice of fostering speaking ability to foreign language acquisition in secondary school students. The research discusses current methods of communicative skill formation, looks into the theoretical basis for speech competence development, and measures different teaching strategies in terms of their impact on students in a contemporary educational setting.
Keywords: Speech competence, foreign language teaching, secondary education, communicative approach, language acquisition.